Tensile and dielectric properties of tin dioxide reinforced deproteinized natural rubber nanocomposites for electrical insulator - Mohamad, Noraiham; Ab Maulod, Hairul Effendy; Abd Razak, Jeefferie; Ghani, Mohd Sharin; Rahim, Nor Hidayah; Mohd Isa, Mohd Hanafiah; Che Halin, Dewi Suriyani; Shueb, Mohammed Iqbal; Ismail, Norshafarina (2023)
Tin dioxide, SnO nanoparticles combined with deproteinized natural rubber could be an effective electrical insulator that inherits its parents’ insulation and conductivity. The deproteinized natural rubber (DPNR) nanocomposites containing uncalcined SnO nanofillers at 0.5, 1.0, 3.0, and 7.0 phr were investigated for tensile and dielectric properties. The